The comprehensive Africa agriculture program as a collective institution - Kolavalli, Shashidhara; Birner, Regina; Flaherty, Kathleen (International Food Policy Research Institute, 2012)
A number of factors favor a collective strategy for African countries to build their reputation regarding improved governance and commitment to agriculture. These include negative spillover effects of poor governance (for example, obstacles to developing regional markets), improved bargaining power of African governments vis-à-vis the donor community, long-standing political efforts to build a positive African identity, and a donor interest in reducing transaction costs by interacting with African countries though regional organizations rather than individually. While realizing these potentials, the CAADP effort to build collective rather than individual reputation involves the classical free-rider problem of collective action: Countries may not honor their commitments after having received increased aid—a strategy that will harm all member countries since it undermines the collective reputation. Since CAADP involves a collective commitment by the donor community as well, donors face similar problems of collective action. They, too, may fail to honor their commitments or revert to individual rather than harmonized approaches to support African agriculture. The paper discusses the strategies that CAADP can use to overcome these collective action challenges.